Effect of Different Organic Potting Media on the Growth, Yield and Quality of Strawberry (Fragaria ananassa) under Greenhouse Condition - Dorji, Pelden; Gurung, Tulsi; Tshomo, Ugyen (Naresuan University Journal: Science and Technology (NUJST), 2023)
The type and composition of potting media are the most influencing factors affecting the growth, fruit quality and yield of strawberry plants. The objective of this study was to evaluate the effects of various organic potting media compositions on the growth, yield and quality parameters of strawberries grown in a greenhouse. The experiment was laid out using randomized complete block design with five treatments consisting of three replications in each treatment. The treatments were compost mix, vermi-compost mix, leaf mold mix, biochar mix and the control (top soil and sand). The growth of the plants grown in different organic potting mixes was measured at 15 days, 30 days, 45 days, 60 days and 75 days after transplantation. Plants grown in leaf mold mix was found to perform well in growth compare to other treatments. Fruit yield parameters such as the number of fruits were highest with vermi-compost mix. The compost mixes also produced best fruit quality attributes like their total soluble solids with 10.84 O Brix. The control produced the lowest results for growth, yield and quality followed by biochar mix media. strawberry production in greenhouse compost mix media is found to have maximum overall effect among other treatments. Keywords: Biochar, Compost, Leaf mold, Strawberry, Vermi-compost